2021
DOI: 10.3889/oamjms.2021.6923
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality among Nurses during the First Year of Coronavirus Disease 2019

Abstract: BACKGROUND: Nurses represent the largest section of the health-care workforce, and lack of sleep has an adverse influence on them, particularly during pandemics such as coronavirus disease 2019 (COVID-19). It causes not only health problem but also poor work results and an increased risk of medical errors. AIM: The goal of the study was to determine the prevalence of poor sleep quality among nurses during COVID-19 outbreaks. MATERIALS AND METHODS: A cross-sectional analysis was conducted among a group of nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…The median number of participants was 338. Excluding manuscripts that reported age as range or median (i.e., 28%) [ 41 , [44] , [45] , [46] , 48 , 59 , [61] , [62] , [63] , 69 , 73 , 75 ], [ 84 , 87 , 96 , [98] , [101] , 104 , 111 , 112 , 121 ], [ 126 , 134 , 137 , 141 , 144 , 145 , 147 ], [ 158 , 161 , [163] , [164] , [165] , 167 , 169 , 175 ], the mean age of the participants was 32.22 ± 9.35 years. Regarding the administered sleep measures, 103 studies reported PSQI scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median number of participants was 338. Excluding manuscripts that reported age as range or median (i.e., 28%) [ 41 , [44] , [45] , [46] , 48 , 59 , [61] , [62] , [63] , 69 , 73 , 75 ], [ 84 , 87 , 96 , [98] , [101] , 104 , 111 , 112 , 121 ], [ 126 , 134 , 137 , 141 , 144 , 145 , 147 ], [ 158 , 161 , [163] , [164] , [165] , 167 , 169 , 175 ], the mean age of the participants was 32.22 ± 9.35 years. Regarding the administered sleep measures, 103 studies reported PSQI scores.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychological impact on nurses has negative consequences for the organization, individual well-being, patient care, and health care systems 4,5,6,7 Research shows that during the COVID-19 outbreak, more than a third of medical personnel experienced symptoms of insomnia, accompanied by depression and anxiety symptoms 8 . Research shows that most nurses have poor sleep quality 9 . Sleep is one of the essential things for physical health for nurses as well as a strong regulator of the immunological process.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that nurses had poor sleep quality during 1 year of the COVID pandemic, but this study did not link sleep quality to nurses' quality of life. 9 Concerning previous studies and the importance of sleep quality and quality of life among nurses in their work caring for COVID-19 patients, the authors aim to determine the correlation between sleep quality and the quality of life among the nurses at Dr. Kariadi General Hospital Center during the COVID-19 pandemic. This study also looks for differences in whether there are differences in sleep quality, quality of life, and quality of life domains between nurses in isolation wards and non-isolation wards; It is hoped that it can add insight to readers, nurses, future researchers, the public, and hospital policymakers regarding sleep quality and quality of life…”
Section: Introductionmentioning
confidence: 99%